Obstacles Facing the Development of Forensic Accounting Curricula within Australian Universities: Exploring Perspectives of Practitioners and Educators - Hashem Al-Shurafat; John Sands; Gregory Jones; Claire Beattie (Australasian Accounting, Business and Finance Journal, 2024)
Forensic accounting education has become an increasingly significant issue in recent years. In Australia, universities have acknowledged the industry’s growing relevance, and there have been attempts to address gaps in the provision of forensic accounting education. Despite these efforts, forensic accounting education is frequently omitted in university programs. This paper seeks to identify the obstacles that influence the transformation of forensic accounting knowledge into university programs. To do so, this study explores the perspectives of two groups: forensic accounting practitioners and university academics. Simi-structured interviews were conducted with the two groups to gather their perception. The findings show that the interdisciplinary nature of forensic accounting, the educator's relevant experience, and some other factors (e.g. university timetabling, calendar, venue arrangements, lack of forensic accounting instructional material, and professional and educational accreditations) are all obstacles facing the development process of forensic accounting. It is recommended for schools that do not have the required resources or are facing many obstacles in integrating forensic accounting education to offer an introductory elective course in the curriculum or utilize appropriately qualified guest speakers. The findings in this qualitative study could help educators in the development process of forensic accounting curricula.
Keywords: Forensic Accounting; Curricula Development; Australia